Effect of the breed and age on the thyroid hormones T3 and T4 concentrations in bovines under tropical conditions Efecto de la raza y la edad sobre las concentraciones de hormonas tiroideas T3 y T4 de bovinos en condiciones tropicales - Campos Gaona Rómulo; Giraldo P Leonidas (Acta Agronómica)
To study the effect of age and breed on blood concentration of thyroid hormones T3 and T4 under the dry tropic conditions, 158 animals from the groups Holstein, Lucerna, Hartón del Valle, Brahman and crossbred F1 Brahman x Brown Swiss were sampled. The animals were allocated in four age groups from newborns calves until eight month old. The average T3 concentration was of 2.25 mmolL-¹ and the T4 was of 57.37 mmolL-¹. The correlation between T3 and T4 was of 0.53. A statistical significant difference (p<0.001) was found for the effects of age breed and group, but not difference was found for the interaction between breed and age (p=0.286). The breeds with higher blood concentrations of T3 and T4 were Holstein and Lucerna. The lowest concentration was found among the crossbred group. The higher concentration of T3 and T4 of thyroid hormones was found in the newborn group. As the calves grow, the concentrations of T3 and T4 decrease progressively. This study found that under dry tropic conditions, in a thermo-neutral borderline zone (according to the THI index) the young bovines show clear differences in the concentration of the thyroid hormones.Key words: Adaptation; Bovine; Growth; Thyroids. Para estudiar el efecto en condiciones de trópico seco de la edad y del grupo racial sobre las concentraciones séricas de las hormonas tiroideas T3 y T4, se muestrearon 158 animales de los grupos raciales Holstein, Lucerna, Hartón del Valle, Cebú Brahman y mestizo F1 (Cebú Brahman x Pardo Suizo), distribuidos en cuatro grupos de edad desde el nacimiento hasta el destete (8 meses). La concentración media de T3 fue 2.25 mmol/L y la de T4, 57.37 mmol/L. La correlación entre T3 y T4 fue de 0.53. Se encontró diferencia estadísticamente significativa para el efecto grupo racial, grupo de edad (P<0.001) pero no para la interacción grupo racial x edad (p=0.286). Los grupos raciales con concentraciones más elevadas fueron Holstein y Lucerna; la concentración más baja se presentó en los bovinos mestizos. La mayor concentración de hormonas tiroideas según la edad ocurrió en recién nacidos, luego descendió progresiva y linealmente. El trabajo encontró que en condiciones de trópico seco, en zona límite de termoneutralidad según el índice ITH, los bovinos jóvenes presentanron diferencias marcadas en las concentraciones de hormonas tiroideas.Palabras claves: Adaptación; Bovinos; Crecimiento; Tiroides.